A Formal Language to Convey Linguistic Information. A Study in Practical Logic - Tsinman, Leonid (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThe author discusses problems of treating formal languages to present linguistic data in machine translation systems or linguistic interfaces for man-computer communication.